Pemberdayaan Ekonomi Keluarga Dhuafa Berbasis Nilai Kemuhammadiyahan: Studi Kasus Keluarga Bapak Julfahmi di Jakarta Timur - Devina Rahma Alya; Najwa Alya Nastiah; Ryan Hidayat; Randy Alifvian (JOURNAL SAINS STUDENT RESEARCH, 2026)
Poverty and limited access to productive economic resources remain major challenges faced by underprivileged families, making empowerment-oriented approaches essential to achieve economic self-reliance. This study aims to examine the process and impact of economic empowerment of an underprivileged family based on Muhammadiyah values, focusing on the family of Mr. Julfahmi in Ciracas District, East Jakarta. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the provision of business capital assistance accompanied by continuous mentoring improves the family’s capacity to manage productive micro-enterprises, increases household income, and encourages a shift in mindset from dependency on consumptive aid toward economic independence. Furthermore, social capital support, active family participation, and the integration of Islamic values and Islamic philanthropy play a significant role in sustaining the family’s business activities. The study concludes that economic empowerment of underprivileged families based on Muhammadiyah values is an effective strategy for enhancing economic independence and family welfare.